Makarenkowskie odczyty o wychowaniu dla rodziców w optyce Foucaultowskiej kategorii urządzania - Maria Szczepska-Pustkowska; Longina Strumska-Cylwik; Małgorzata Lewartowska-Zychowicz (Problemy Wczesnej Edukacji)
The subject of our interest is the rhetoric of Makarenko’s readings/interpretations of upbringing designated for parents. We would like to subject it to consideration in the prospect/perspective of Foucault’s governmentality category, understood as a specific metacategory/joint category connecting the axes of power (the Soviet power), knowledge (political economy), and the subject (homo sovieticus). Applying the governmentality category provides for the possibility of attempting to reconstruct traces of tangle/discursive relations and undiscursive elements of the policy of arranging a family which is a component of a broader policy of the Soviet state aimed at “forging” the new Soviet man. In this context, we will recognize Makarenko’s pedagogy as a kind of conceptualization and implementation of the policy of the Soviet state at the family level, having the goal of shaping a man of collective mentality, completely subordinated to the Soviet state, with standardized and ideologized consciousness.